Infantile bullous pemphigoid successfully treated with intravenous immunoglobulin therapy. (22nd May 2017) - Watanabe, T.; Hara, S.; Muto, J.; Watanabe, D.; Akiyama, M.
Abstract : Clickhere for the corresponding questions to this CME article.